Marketing to occasional sporting event tourists: profiles, travelling patterns, and information channels. Issue 2 (4th May 2017) - Katsoni, Vicky; Vrondou, Ourania
ABSTRACT: The coexistence of sports and tourism, bridging these two worlds of different social activities, participants and providers, has produced numerous studies due to the unlimited theoretical potential of this area. However, authors are increasingly realizing the infinite spectrum of sports tourism, as well as the need for further clarification of all aspects involved in this form of tourism. The lack of sports tourist profiling is more evident in the sporting events tourism spectrum, despite the large numbers of participants such events tend to attract. This study aims to illuminate one of the largest and most underexplored segments of sporting events tourism, that of 'tourists interested in watching sporting events during their vacation' or 'occasional sports tourists'. A descriptive statistical analysis of 765 usable questionnaires, collected at the tourism destination of Arcadia in Greece, improved our understanding of the size of this segment of the tourism industry, the profiles and travelling patterns of its customers, as well as their information-sourcing behaviour. Watching sporting events during their vacation is more common amongst young men (up to 35 years old) who present an independent travelling mode, and seek information through available technology rather than personal communication. Effective channelling of information could reach and exploit the 'occasional sport tourism' market, and could support effective marketing strategies for destinations seeking to enrich their local tourism experience.